Association of Mediterranean diet adherence during pregnancy with maternal and neonatal lipid, glycemic and inflammatory markers: The GESTAFIT project - Marta Flor‐Alemany; Pedro Acosta‐Manzano; Jairo H. Migueles; Laura Baena‐García; Pilar Aranda; Virginia A. Aparicio (Wiley, 2023)
Abstract To examine the association of Mediterranean diet (MD) adherence during pregnancy with maternal and neonatal lipid, glycemic, and inflammatory markers. This study included 152 women from the GESTAFIT trial and a subsample of 35 newborns. The Mediterranean Diet Score, derived from food frequency questionnaires, was employed to assess MD adherence. Total cholesterol, high‐density lipoprotein‐cholesterol (HDL‐C), low‐density lipoprotein‐cholesterol (LDL‐C), triglycerides, and glucose were assessed in the mother (at the 16th and 34th gestational weeks [g.w.]) and in cord arterial and venous serum with standard procedures using an autoanalyzer. Pro‐inflammatory and anti‐inflammatory cytokines (interleukin [IL]−6, IL‐8, IL‐10, IL‐1beta, interferon gamma, and tumour necrosis factor alpha [TNF‐α]) were measured with Luminex xMAP technology. A greater MD adherence was associated with higher HDL‐C and lower LDL‐C, LDL‐C/HDL‐C ratio, triglycerides, triglycerides/HDL‐C ratio, and TNF‐α in the mother at the 16th and the 34th g.w. (|β|: 0.191-0.388, p < 0.05). A higher intake of whole grain cereals, fruits, vegetables and fish and a lower intake of sweets were associated with higher HDL‐C and lower LDL‐C, LDL‐C/HDL‐C ratio, triglycerides, triglycerides/HDL‐C ratio, and TNF‐α at the 16th and 34th g.w. (|β|: 0.188-0.334, p < 0.05). No associations were found with the cord arterial and venous serum markers (p > 0.05). A greater MD adherence during pregnancy, driven by a higher intake of whole grain cereals, fruits, vegetables and fish, and a lower intake of sweets, was positively associated with the maternal lipid and inflammatory serum markers throughout gestation. MD adherence during pregnancy was not associated with cord serum markers.